A lightweight mutual authentication approach for RFID tags in IoT devices. (2018) - Tewari, Aakanksha; Gupta, B.B.
In this paper, we present an approach for mutual authentication between server and RFID tags using hash and bitwise computations. The use of RFID technology is changing frequently these days, and their use is widespread. Due to the persistent development of radio frequency identification (RFID), substantial amount of attention has been drawn towards the security issues in RFID from researchers and industries. Mutual authentication between server and the RFID tags is one of the most popular mechanisms to protect these systems from attacks, providing confidentiality, integrity and authentication. But security and privacy issues are also increasing with time as it low cost and have limited resources we need to minimise the computations and storage cost of a protocol too. Our protocol is simple and also ensures the security against various attacks. The security and performance analysis also verifies the strength of our protocol.